Surface electromyography in the assessment of masticatory muscle activity in patients with pain-related temporomandibular disorders: a systematic review - Szyszka-Sommerfeld, Liliana; Sycińska-Dziarnowska, Magdalena; Spagnuolo, Gianrico; Woźniak, Krzysztof (Frontiers in Neurology, 2023)
Background Temporomandibular disorders (TMD) are a set of painful conditions affecting the orofacial region that are prevalent and constitute the most frequent type of non-dental pain complaint in the maxillofacial area. Pain-related TMD (TMD-P) is characterized by ongoing pain in the masticatory muscles, the temporomandibular joint, or surrounding structures. Due to the multiple factors that contribute to the development of this condition, it can be challenging to accurately diagnose. One of the useful method for assessing patients with TMD-P is surface electromyography (sEMG). The aim of this systematic review was to provide a comprehensive overview of the current scientific literature on the evaluation of masticatory muscle activity (MMA) in individuals diagnosed with TMD-P, through the utilization of sEMG. Methods To gather relevant information, electronic databases such as PubMed, Web of Science, Scopus, and Embase were searched using specific keywords including: “pain” AND (“temporomandibular disorder*” OR “temporomandibular dysfunction*”) AND “surface electromyography” AND “masticatory muscle activity.” The inclusion criteria were studies assessing MMA in patients with TMD-P using sEMG. The Effective Public Health Practice Project (EPHPP) Quality Assessment Tool for Quantitative Studies was utilized to evaluate the quality of the studies that were included in the review. Results The search strategy identified 450 potential articles. Fourteen papers met the inclusion criteria. Global quality rating for significant part of the articles was weak. Most studies showed greater sEMG activity of the masseter (MM) and temporal anterior (TA) muscles at rest in TMD-P subjects than in the asymptomatic controls, while the MM and TA muscles were less active in the pain-related TMD group compared to the non-TMD group during maximal voluntary clenching (MVC). Conclusion There were differences in MMA in the TMD-pain population compared to a healthy control group during various tasks. The diagnostic efficacy of surface electromyography in assessing individuals with TMD-P remains unclear.